Prayer-marks Heralding Acute Coronary Syndrome - Aggarwal, Sourabh (Journal of Health, Population and Nutrition, 2012)
<!–[if gte mso 9]> <![endif][if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9905 JHPN 2011; 29(6): 660 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9905 JHPN 2011; 29(6): 660<span style="font-size: 9.5pt; font-family: "StoneSerifStd-Medium","serif"; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: StoneSerifStd-Medium; mso-fareast-language: EN-US;">